2015
DOI: 10.1080/15438627.2015.1005297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Athletic Training on the Spinal Curvature in Child Athletes

Abstract: The purpose of this study was to examine the spinal posture in young athletes depending on training intensity. The spinal curvature of 245 children, age 8 to 12 years, was evaluated using rasterstereography. According to their weekly training time group 1 (mean age: 9.54 ± 1.18) did 2-6, group 2 (mean age: 9.49 ± 0.87) did 6-15 and group 3 (mean age: 9.68 ± 0.87) did over 15 hours of training. Group 1 had a significantly higher weight (p = 0.028) (33.86 ± 7. kg) than those of the more active groups (30.67 ± 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
2
7
0
1
Order By: Relevance
“…serves or attacks. These results are in line with the findings of other researchers, who assumed that sports training might affect the position of the shoulder girdle, scapulae, pelvic alignment and spinal curvatures due to the specific movement patterns [3,4,9,14,23,29]. Oyama et al (2008) observed in overhead athletes that the dominant side scapula was more internally rotated and anteriorly tilted than the non-dominant side scapula.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…serves or attacks. These results are in line with the findings of other researchers, who assumed that sports training might affect the position of the shoulder girdle, scapulae, pelvic alignment and spinal curvatures due to the specific movement patterns [3,4,9,14,23,29]. Oyama et al (2008) observed in overhead athletes that the dominant side scapula was more internally rotated and anteriorly tilted than the non-dominant side scapula.…”
Section: Discussionsupporting
confidence: 92%
“…Those authors also noted that training experience was related to the considerable asymmetry of the shoulder girdle [2]. On the other hand, based on a study that included 245 athletes between 8 and 12 years, the authors stated that a high level of athletic training could lead to a decrease in the lateral deviation of the spine [3]. Walaszek et al (2018) observed a corrective effect of regular 6-month judo training, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their program consisted of strengthening and stretching exercises, but they did not include body perception exercises. Other studies only focused on thoracic kyphosis and outlined its improvement by an athletic training ( Betsch et al, 2015 ). Bansal et al (2014) summarized in a review that exercises may result in a modest improvement of (thoracic) posture.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several scientific studies have assessed spinal morphology in young athletes as professional soccer players (Sainz de Baranda et al, 2001), basketball players (Ferreira-Guedes & Amado-João, 2014;Grabara, 2016), handball players (Grabara, 2014), volleyball players (Grabara, 2015), rhythmic gymnasts (F. Martínez-Gallego & Rodríguez- García, 2005;Ohlén et al, 1989), swimmers (Pastor, Santonja, Ferrer, Domínguez, & Canteras, 2002;Santonja & Pastor, 2000), dancers of Spanish and Classical dance (Gómez- Lozano, 2007), cricket players (Hecimovich & Stomski, 2016), cross-country skiers (Alricsson et al, 2016) and wrestling (Rajabi, Doherty, Goodarzi, & Hemayattalab, 2008). Other studies, included athletes of different sports (Betsch et al, 2015;Grabara, 2014;Lichota, Plandowska, & Mil, 2011;Wojtys et al, 2000). However, to the best of our knowledge, no study has assessed the implications of Inline Hockey (IH) practice on "Sagittal Integrative Spinal Morphotype" in adolescent players.…”
Section: Introductionmentioning
confidence: 99%